Content Marketing Analysis of Batik MSMEs in Enhancing Brand Awareness Through Instagram (A Case Study of the Instagram Account @Simkuring_Batikcianjur) - Riska Lapiana Huki; Eddy Soeryanto Soegoto; Rahma Wahdiniwaty; Irfan Dwiguna Sumitra; Adam Mukharil Bakhtiar (Jurnal Manajemen Perbankan Keuangan Nitro, 2026)
The rapid development of digital technology has forced Micro, Small, and Medium Enterprises (MSMEs) to implement marketing strategies packaged through digital platforms. This study aims to analyze how the content marketing strategy of the Simkuring Batik Cianjur MSME increases brand awareness through the Instagram account @simkuring_batikcianjur. To obtain in-depth research results, this study used a descriptive qualitative method with a case study approach. Data were obtained through unstructured interviews, direct observation and documentation, and through the @simkuring_batikcianjur Instagram account (technical triangulation) to ensure consistency of information. The findings indicate that content marketing implementation is carried out through four stages: goal setting, audience mapping, content ideation and creation, and distribution and amplification. This study concludes that implementing content marketing that aligns with the MSME's reasons for being established and its direct involvement in the events that initiated the MSME, along with continuous product innovation, will create brand awareness across various groups, fostering long-term relationships with customers.